Pengaruh Keragaman Dewan Direksi Terhadap Kinerja Keuangan Perusahaan - Roika, Roika; Salim, Ubud; Sumiati, Sumiati (IQTISHODUNA, 2019)
In implementing corporate governance, the diversity of the board of directors is an essential component. The most frequently observed diversity of the board is gender diversity, and along with the increasing internationalization of business today, the nationalities diversity is also one of the interesting types of analysis to be analyzed. The purpose of this study is to investigate the influence of the diversity of the board of directors on the performance of the company. The company performance examined in this study is the firm financial performance measured by using ROE and firm value measured by the Tobin's Q ratio. The population of this study are all non-financial companies listed on the Indonesia Stock Exchange in 2016-2017. Following the same selection criteria in this study, 33 sample companies were screened. The results of hypothesis testing with multiple regression indicate that only nationalities diversity influences the firm financial performance as measured by ROE. While gender diversity has a negative effect on firm financial performance as measured by ROE. And gender diversity and nationalities diversity does not affect the firm value